A critical analysis of the child justice system in (mainland) Tanzania - Bakta, Seraphina Msengi (Department of Public Law, 2016)
This study critically examines the child justice system in mainland Tanzania in the light of principles recommended by international child rights law. Thus far, international child rights law has developed a three-dimensional approach to child justice: an effective system to prevent child delinquency, the use of non-judicial procedures, and the development of special procedures aimed at protecting the rights of the child when judicial interventions are unavoidable. This approach is consistent with modern philosophical thinking about child justice. The analysis of Tanzania's policies and laws on the prevention of child delinquency revealed glaring inadequacies. In particular, the laws fail to provide adequate legal protection to their socio-economic rights, such as those relating to health services and education. Since children subjected to violence and those lacking access to the basic necessities of life are the most prone to delinquency, the lack of policy attention to these areas mean that most of those children are likely to continue to engage in delinquency. Tanzania's child justice system places undue reliance on judicial mechanisms. Although an attempt has been made of late to introduce some provisions allowing for the use of non-judicial interventions, these lack sufficient legal foundation and are not used consistently. Despite its reliance on judicial mechanisms, Tanzania's child justice system is not as child friendly as one would expect. Granted, judicial mechanisms make provision for the child's rights to information, to be heard, to privacy and to an expeditious process. However, they do not adequately protect the child's rights to legal representation and to protection against prosecution for status offences. Sentences such as repatriation, detention at the President's pleasure and corporal punishment, which are inconsistent with international law, are still legally allowed. Substantial reforms are required in order to make Tanzania's child justice system compliant with international law and modern notions of justice. The reforms that have been made through the recently enacted Law of the Child Act 2009 are commendable but, as this thesis shows, much more remains to be done in order to guarantee in full the rights of the child in Tanzania's child justice system.